The influence of the disordered dipole subsystem on the thermal conductivity of the CO solid at low temperatures - Sumarokov, V.; Jeżowski, A.; Stachowiak, P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The thermal conductivity of solid CO was investigated in the temperature range 1–20 K. The experimentaltemperature dependence of thermal conductivity of solid CO was described using the time-relaxation method within the Debye model. The comparison of the experimental temperature dependences of the thermal conductivity of N2 and CO shows that in the case of CO there is an additional large phonon scattering at temperatures near the maximum. The analysis of the experimental data indicates that this scattering is caused by the frozen disordered dipole subsystem similar to a dipole glass. The scattering is described by theresonant phonon scattering on tunnelling states and on low-energy quasi-harmonic oscillations within thesoft potential model.